MR Findings in AIDS-Associated Myelopathy - Chong, June (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: The most common cause of spinal cord disease among patients with AIDS or those infected with HIV-1 is AIDS-associated myelopathy. The purpose of this study was to determine the MR characteristics of the spinal cord in this patient population and to correlate these findings with the clinical severity of myelopathy. METHODS: MR images of the spinal cord in 21 patients with documented HIV-1 infection or AIDS and a clinical diagnosis of AIDS-associated myelopathy were assessed retrospectively for atrophy, intrinsic signal abnormality, and abnormal enhancement. The clinical severity of myelopathy was graded by a neurologist on the basis of physical examination, and a qualitative correlation was made with the MR findings. RESULTS: MR findings were abnormal in 18 of the 21 patients. The most common feature was spinal cord atrophy (n = 15), typically involving the thoracic cord with or without cervical cord involvement, followed by intrinsic cord signal abnormality (n = 6), and normal-appearing cord (n = 3). Three patients had both cord atrophy and intrinsic cord signal abnormality. The cord signal abnormality was diffuse, without predilection for any specific distribution pattern. Enhancement was not seen in any of the 10 patients who received intravenous contrast material. Only one of 16 patients with moderate to severe myelopathy had normal MR findings, as compared with two of five patients with mild myelopathy. CONCLUSION: MR findings in the spinal cord are abnormal in the majority of patients with AIDS-associated myelopathy, typically showing spinal cord atrophy, with or without intrinsic cord signal abnormality. Patients with moderate to severe myelopathy have an increased frequency of spinal cord abnormalities, but a definite correlation between clinical severity of myelopathy and extent of MR abnormalities remains to be established.